If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + 0 = -2y Combine like terms: 6 + 0 = 6 6 = -2y Solving 6 = -2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2y' to each side of the equation. 6 + 2y = -2y + 2y Combine like terms: -2y + 2y = 0 6 + 2y = 0 Add '-6' to each side of the equation. 6 + -6 + 2y = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 2y = 0 + -6 2y = 0 + -6 Combine like terms: 0 + -6 = -6 2y = -6 Divide each side by '2'. y = -3 Simplifying y = -3
| kx^3=5x+2 | | lny+4x=x+3lnx | | 5x/10=13x-10 | | 35x+23y=16xy | | 36=2(v+8)-6v | | 24+3=2x+x | | 23+54-x= | | -12x-16x-3=-4(3x-2)-8x | | -2.3n+16=-5n-38 | | log-2b=3 | | 19-x=-2 | | 2/3t=-1/5 | | 5x+13+2=5x+4+7 | | 2.1=7 | | 2cos^2x+1=cosx | | 2x^2+40x+168=0 | | 2+4(3+x)=18 | | C=15n+50 | | 7n+5-2n=20+3n+1 | | 0.60x+1.50+10=13.50 | | 10x+20y+30z=10460 | | 3(-0.4u+1.8)= | | 2/3(x-15)=26 | | 2/3(x-15)=14 | | 1/2(x-0.3)=1.55 | | 7a+2b=5000 | | 2(x+5)-3=7 | | 6e^5x-3=18 | | 1p+.80=2p+.65 | | 3x^2-16=20 | | 2.8(-1+2n)= | | 14c+2=20c+1.50 |